Scooby-Doo! and the Fiendish Funfair - McCann, Jesse Leon (BBC Worldwide Ltd, 2000)
A wealthy jeweller has vanished and a deserted funfair is coming alive with monsters.The gang are on the case- and so are you!
Keywords: Juvenile literature-Fiction